Role of duplex scanning in differentiating acute embolic from thrombotic limb ischemia - Ahmed Mohamed Talaat Elgengehe; Essam Baligh Ewes; Soliman Ghareeb Ibrahim; Waleed Abdelsalam Ammaar (Cairo : Ahmed Mohamed Talaat Elgengehe, 2010)
Acute limb ischemia represents an emergency in which restoration of perfusion through early intervention can lead to limb salvage, whereas deayed intervention may result in significant morbidity, including limb loss and potentially, death. To prove the accuracy and reliability of duplex scanning in differentiating embolic from thrombotic acute arterial occlusion, and to test the role of post-operative duplex in confirming the pre-operative findings
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Cardiology
Issued also as CD
Keywords: Acute limb ischemia; Duplex scanning; Embolic and thrombotic occlusion